Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2319/040612-287.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the mechanical behavior of nickel-titanium orthodontic initial archwires

Abstract: Objectives: To investigate and compare the characteristics of commonly used types of traditional and heat-activated initial archwires at different temperatures by plotting their load/deflection graphs and quantifying three parameters describing the discharge plateau phase. Materials and Methods: Forty-eight archwires of cross-sectional diameters ranging from 0.010 inches to 0.016 inches were obtained from seven different manufacturers. A modified three-point wire-bending test was performed on three analogous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 17 publications
3
48
0
2
Order By: Relevance
“…Just a mild enhancement in mechanical properties was observed in the loading/deflection curves when compared with SE wires. This fact is in accordance with conclusions of Lombardo et al who observed lighter forces and longer plateau from HA wires 12 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Just a mild enhancement in mechanical properties was observed in the loading/deflection curves when compared with SE wires. This fact is in accordance with conclusions of Lombardo et al who observed lighter forces and longer plateau from HA wires 12 .…”
Section: Discussionsupporting
confidence: 83%
“…In this work (Table 3), permanent strain was irrelevant for all groups evaluated since all specimens showed a shape recovery to 99% of its original shape. Similar results were presented by Lombardo et.al even when 4-mm bending was performed at 55 °C [12] . The archwire resistance to attachment into bracket slots and intensity force delivery to teeth on unloading are mechanical factors that affect the tooth movement.…”
Section: Mse1supporting
confidence: 79%
“…Super-elastic copper nickel titanium (CuNiTi) wires are even more predictable, exerting constant forces over a wide deflection range, meaning that the load remains the same even as the teeth begin to align. 9,10 Clear aligners, on the other hand, are viscoelastic, having intermediate properties between those of viscous and elastic materials. 11 This means that under loading their behavior may vary considerably over time, even when first inserted and before any tooth movement is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic adsorption spectrometer analysis is an effective, dependable, and feasible method to evaluate the amount of ion released from orthodontic wires in aqueous solutions [27,33]. It has been reported that temperature changes influence the physical and chemical properties of dental materials and most orthodontic appliances [22,24,26]. Thus, the current study aimed to evaluate the effect of pH changes and thermocycling, as the two main factors that change many times during the day after each meal and drink, on the amount of Ni released from orthodontic appliances.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors may lead to the release of toxic metal ions, such as Ni, from alloys [21]. Many authors have questioned the effect of temperature changes on orthodontic alloys [22][23][24]. Due to these thermal stresses, microstructural changes can take place, remarkably changing the physical properties of the dental material [24,25].…”
Section: Introductionmentioning
confidence: 97%